Molecular Aspects of Adipose-Derived Stromal Cell Senescence in a Long-Term Culture: A Potential Role of Inflammatory Pathways - Marta Pokrywczynska (Cell Transplantation, 2020)
Long-term culture of mesenchymal stromal/stem cells in vitro leads to their senescence. It is very important to define the maximal passage to which the mesenchymal stromal/stem cells maintain their regenerative properties and can be used for cellular therapies and construction of neo-organs for clinical application. Adipose-derived stromal/stem cells were isolated from porcine adipose tissue. Immunophenotype, population doubling time, viability using bromodeoxyuridine assay, MTT assay, clonogencity, β-galactosidase activity, specific senescence-associated gene expression, apoptosis, and cell cycle of adipose-derived mesenchymal stromal/stem cells (AD-MSCs) were analyzed. All analyses were performed through 12 passages (P). Decreasing viability and proliferative potential of AD-MSCs with subsequent passages together with prolonged population doubling time were observed. Expression of β-galactosidase gradually increased after P6. Differentiation potential of AD-MSCs into adipogenic, chondrogenic, and osteogenic lineages decreased at the end of culture (P10). No changes in the cell cycle, the number of apoptotic cells and expression of specific AD-MSC markers during the long-term culture were revealed. Molecular analysis showed increased expression of genes involved in activation of inflammatory response. AD-MSCs can be cultured for in vivo applications without loss of their properties up to P6.